Brillouin super-cooling/heating in a non-Hermitian phononic dimer - Yicheng Zhu; Boyi Xue; Yuncong Sun; Qi Geng; Yuping Chen; Xianfeng Chen; Xiaoshun Jiang; Li Ge; Wenjie Wan (Proceedings of the National Academy of Sciences, 2025)
The ability to coherently manipulate phonons through light permits cooling and heating microscale quantum systems for various critical fields in metrology, information processing, and sensing. However, these physical systems often are hard to isolate and open for exchanging energy externally, making themselves non-Hermitian. Here, we experimentally observe a super-cooling/heating state in a non-Hermitian phononic dimer, where the two independent phonon modes of distinct cooling/heating rates become synchronous in cooling/heating. Such super cooling/heating is manifested in a Parity–Time symmetric state controlled by two counterpropagating optical pumps. These results reveal the non-Hermitian nature of the phonon dimer and illustrate a coherent technique for synchronous cooling/heating non-Hermitian systems, paving the way for practical applications in quantum sensing and metrology.